1990
DOI: 10.1021/ja00158a057
|View full text |Cite
|
Sign up to set email alerts
|

Ring opening and oligomerization of thiirane by hexaosmium carbonyl cluster complexes

Abstract: Metal complexes have played central roles in the initiation and propagation of many important polymerization reactions.1 Studies of the reactions of metal carbonyl cluster complexes with episulfides have shown sulfur transfer and alkene elimination to be the preferred reaction pathway (e.g., eq l).2 Although thiirane, C2H4S, is able to serve as a ligand through coordination of the sulfur atom,3 very little is known about the nature of the ring opening and eventual elimination of alkene in these reactions. The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

1990
1990
2001
2001

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 4 publications
1
15
0
Order By: Relevance
“…In this report we describe the synthesis and structure of the new compound Mn 2 (µ-SCH 2 CH 2 S)(CO) 7 , 1, and the syntheses and structures of a series of its phosphinesubstituted derivatives. All of these compounds contain a bridging ethanedithiolato ligand and a bridging carbonyl ligand that exhibits varying degrees of asymmetric semibridging coordination that appears to be dependent on the nature of the phosphine ligand coordinations.…”
Section: Introductionmentioning
confidence: 99%
“…In this report we describe the synthesis and structure of the new compound Mn 2 (µ-SCH 2 CH 2 S)(CO) 7 , 1, and the syntheses and structures of a series of its phosphinesubstituted derivatives. All of these compounds contain a bridging ethanedithiolato ligand and a bridging carbonyl ligand that exhibits varying degrees of asymmetric semibridging coordination that appears to be dependent on the nature of the phosphine ligand coordinations.…”
Section: Introductionmentioning
confidence: 99%
“…Other unsaturated molecules like olefm, MeaCC=N, acetone, and internal acetylenes do not insert readily.% Since 8-hydrogen-containing complexes Cp*,TiFt are liable to lose olefin, and insertion into the Ti-H bond is much faster than insertion into the T i 4 bond, the reactivity of the Cp*,TiR compounds is completely dominated by net 8-hydrogen-transfer reactions. The reactivity of 2 therefore closely resembles that of Cp*2TiH.12J3b For the strongly Lewis acidic, do, group 3 and lanthanide element compounds Cp*,MR, 8-hydrogen elimination, although kinetically within reach, normally competm with other pathways like 8-alkyl eliminations and allylic and vinylic C-H activations. "s6 These reactions are not observed for compounds Cp*,TiR, resulting in relatively simple reactivity patterns.…”
Section: Tervalent Titanium Compounds ($-Cande5)2tirmentioning
confidence: 91%
“…A generally applicable method has been worked out to sidestep these problems of characterization. Cp*,TiR compounds can be readily converted into their diamagnetic monochloride analogues Cp*,Ti(R)Cl by oxidation with PbCl, (eq 3).14b The latter compounds are Cp*,TiR + f/zPbC12 -Cp*,Ti(R)Cl+ 7,Pb (3) easily identified by conventional NMR methods. This technique has extensively been applied in this study to demonstrate the presene of ligand R or X in paramagnetic compounds Cp*,TiX and Cp*,TiR obtained from Cp*,TiMe and Cp*,TiEt and reported in this or previous papers.13 In addition to the fact that oxidation to Cp*,Ti(R)Cl is very helpful for identification, the method also is an excellent synthetic route to new mixed hydrocarbyl compounds Cp*,Ti(R)R'.…”
Section: (2) -18 7 (2)mentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been shown that thiirane can react with metal clusters without the complete elimination of the hydrocarbon fragment, as shown by the formation of complexes containing dithiolato ligands from the reactions of thiirane with Os 6 (CO) 17 (NCMe) and Os 6 (CO) 16 (NCMe) 2 (eq 2) …”
Section: Introductionmentioning
confidence: 99%